SOME COMMENTS ON JADID LITERATURE (American Journal of Interdisciplinary Research and Development, 2022)
This article examines the main ideas of the representatives of modern literature, the commonalities in their work, the views of Fitrat, Behbudi, and Nosirkhan Tura on the role of sending students abroad in the development of the country. In fiction, it is argued that the renewal of the spiritual world of the heroes, the expansion of their worldview, can raise the morale of the nation and bring it to a new stage of development. The transition of nationalist ideas to the work of art and from it to life is considered.